The intertemporal evolution of agriculture and labor over a rapid structural transformation: Lessons from Vietnam - Liu, Yanyan; Barrett, Christopher B.; Pham, Trinh; Violette, William (Elsevier, 2020)
We combine nationally representative household and labor force survey data from 1992 to 2016 to provide a detailed description of rural labor market evolution and how it relates to the structural transformation of rural Vietnam, especially within the agricultural sector. Our study adds to the emerging literature on structural transformation in low-income countries using micro-level data and helps to answer several policy-related questions. We find limited employment creation potential of agriculture, especially for youth. Rural-urban real wage convergence has gone hand-in-hand with increased diversification of the rural economy into the non-farm sector nationwide and rapid advances in educational attainment in all sectors’ and regions’ workforce. Minimum wage laws seem to have played no significant role in increasing agricultural wages. This enhanced integration also manifests in steady attenuation of the longstanding inverse farm size-yield relationship. Farming has remained securely household-based and the family farmland distribution has remained largely unchanged. Small farm sizes have not obstructed mechanization nor the uptake of labor-saving pesticides, consistent with factor substitution induced by rising real wage rates. As rural households rely more heavily on the labor market, human capital accumulation (rather than land endowments) have become the key correlate of improvements in rural household well-being.